2020
DOI: 10.24251/hicss.2020.589
|View full text |Cite
|
Sign up to set email alerts
|

Retentivity Beats prior Knowledge as Predictor for the Acquisition and Adaptation of New Production Processes

Abstract: In the time of digitalization the demand for organizational change is rising and demands ways to cope with fundamental changes on the organizational as well as individual level. As a basis, learning and forgetting mechanisms need to be understood in order to guide a change process efficiently and successfully. Our research aims to get a better understanding of individual differences and mechanisms in the change context by performing an experiment where individuals learn and later re-learn a complex production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The results showed that reflection facilitates U/IF and work engagement through critical reflection. 1 Haase et al (2020) used a similar lab-based production context and showed in a pre-post-test design with 41 participants within a group design that the participants’ retentivity (as a facet of intelligence) largely explained variance in individual differences in intentional forgetting performance.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that reflection facilitates U/IF and work engagement through critical reflection. 1 Haase et al (2020) used a similar lab-based production context and showed in a pre-post-test design with 41 participants within a group design that the participants’ retentivity (as a facet of intelligence) largely explained variance in individual differences in intentional forgetting performance.…”
Section: Resultsmentioning
confidence: 99%
“…Individual forgetting is a precondition for organizational forgetting (Akhshik, 2014;Cegarra-Navarro & Moya, 2005), and similar to every human behavior, its success depends on various dispositional and situational factors (Niessen et al, 2020). For example, past research has shown that cognitive abilities are of particular importance for adaptation (e.g., Haase et al, 2020;Jundt et al, 2015). Situational factors, such as the environmental characteristics of a change situation, also have an impact on adaptive performance (Niessen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%